The Effect of Hand Washing Soap with Soursop Leaf and Guava Leaf Extract on Staphylococcus aureus Bacteria - Indah Zahara; Agustina Nina (Universitas Aisyah Pringsewu, 2023)
This study tested a handwash formulation containing a combination of soursop leaf extract and guava leaf extract as active ingredients. These two extracts are known to have antibacterial properties, and the study results show that the formulated handwash has physical and chemical properties according to SNI standards. The formulated handwash has a brown color with a distinctive aroma of extract, homogeneous, pH 10.00, foam height of 100 mm, and viscosity ranging from 700-20,000 cPs with pseudoplastic flow properties. In addition, handwashing with a combination of soursop and guava leaf extract also showed significant antibacterial activity against Staphylococcus aureus bacteria. The average diameter of the inhibition zone for handwash with different formulas showed powerful results. Thus, combining soursop leaf extract and guava leaf extract can be an effective alternative in maintaining hand hygiene and preventing disease transmission through contact with microorganisms on the hands. Further research needs to be done to optimize the use of natural ingredients such as soursop leaf extract and guava leaf extract in health care products to provide more comprehensive benefits to maintain the health and cleanliness of the body. Abstrak: Penelitian ini menguji formulasi handwash yang mengandung kombinasi ekstrak daun sirsak dan ekstrak daun jambu biji sebagai bahan aktif. Kedua ekstrak ini diketahui memiliki sifat antibakteri, dan hasil penelitian menunjukkan bahwa handwash yang diformulasikan memiliki sifat fisik dan kimia yang sesuai dengan standar SNI. Handwash yang diformulasikan memiliki sediaan berwarna cokelat dengan aroma khas ekstrak, homogen, pH 10,00, tinggi busa 100 mm, dan viskositas berkisar antara 700-20.000 cPs dengan sifat alir pseudoplastis. Selain itu, handwash dengan kombinasi ekstrak daun sirsak dan ekstrak daun jambu biji juga menunjukkan aktivitas antibakteri yang signifikan terhadap bakteri Staphylococcus aureus. Diameter rata-rata zona hambat untuk handwash dengan formula yang berbeda menunjukkan hasil yang sangat kuat. Dengan demikian, kombinasi ekstrak daun sirsak dan ekstrak daun jambu biji dapat menjadi alternatif efektif dalam menjaga kebersihan tangan dan mencegah penularan penyakit melalui kontak mikroorganisme pada tangan. Penelitian lebih lanjut perlu dilakukan untuk mengoptimalkan penggunaan bahan alami seperti ekstrak daun sirsak dan ekstrak daun jambu biji dalam produk perawatan kesehatan, guna memberikan manfaat yang lebih luas dalam upaya menjaga kesehatan dan kebersihan tubuh.